Lattice paths: Coding and complexity - (:unkn) unknown (IEEE Computer Society, 2009)
We shall study several sequences of numbers arising in the array (n; k) = 3 · (n+k/k) - 2 · (n+k/k-1) . Some of them relate to an old problem of Berlekamp, which arose in the construction of certain convolutional burst-error detecting codes. The other sequences are of recent interest in combinatorial theory. © 2009 IEEE.